Space story - Ostby, Fiona (West Margin Press, 2022)
"Two people fall in love on earth and have a child together. But as the planet becomes uninhabitable and everyone starts evacuating to the space station orbiting above, the family gets separated. Told in three interwoven stories, this graphic novel follows the journey of Hannah, Leah, and Bird as they experience love and loss, joy, loneliness, desperation, and hope for a new future"--